ANÁLISE DE INDICADORES DA QUALIDADE VOLTADOS À SUSTENTABILIDADE - Amaral, Tatiana; Camargo Filho, Carlos Augusto; Soares, Bruno; Resende, Fabiana Barbosa de; Silva, Jorge Luiz R. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Sistema de Avaliação da Conformidade de Empresas de Serviços e Obras da Construção Civil (SiAC) is one of the projects that are part of the Programa Brasileiro de Qualidade e Produtividade no Habitat (PBQP-h), and aims to evaluate the compliance of the Management Systems of the Quality of service and works companies, aiming to contribute to the evolution of quality, productivity and sustainability in the sector. The program requires construction companies to monitor sustainability-related quality indicators at the construction site. The objective of this work is to present and discuss the results of the monitoring of sustainability indicators in the incorporating and construction companies in Goiás, comparing the results of the indicators between the companies and the type of enterprise. For this, surveys of the indicators required by the SiAC were carried out in four construction companies in Goiás through questionnaires. With the results obtained from the analysis and compilation of the data, it was possible to analyze the relationship between the results, the practices adopted by the construction company and the type of builds.